Archaeology and the built environment of early medieval England. (April 2019) - Wright, Duncan W.
Abstract : The bulk of people we can now be assured, were content with something that hardly deserves a better title than that of a hovel […] in such cabins, with bare head room, amid a filthy litter of broken bones, of food and shattered pottery […] lived the Anglo-Saxons (Leeds 1936: 25–26). This quote from E.T. Leeds, a pioneer of Anglo-Saxon archaeology during the first half of the twentieth century, was inspired by his excavation of settlement remains at Sutton Courtenay, then in Berkshire. Leeds's excavations were actually a breakthrough moment, resulting in the first identification of early medieval settlement structures other than those associated with ecclesiastical sites. In spite of this, the frustration and disappointment with the character and quality of the Sutton Courtenay site are all too apparent in Leeds's assessment. As an expert in Anglo-Saxon artwork, how could he reconcile the skill and craft of fine metalwork, with the ephemeral and impoverished settlement with which he was now dealing? Likewise, where were the great charismatic halls of monumental construction that populated such literary sources as Beowulf ? The excavation of the graves of Sutton Hoo, two years after investigations at Sutton Courtney came to a close, served only to amplify the disparity between settlement and burial archaeology—put simply, burials were viewed as richer, grander and far more interesting.